Effects of adding saturated fat to diets with sorghum-based dried distillers grains with solubles on growth performance and carcass characteristics in finishing pigs - C Feoli; Donald H Kropf; S Issa; Terry L Gugle; S D Carter; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 2008)
Two experiments were conducted to determine the effects of adding sources of saturated fat to diets with sorghum-based dried distillers grains with solubles (DDGS). For Exp. 1, 112 barrows (initially 140 lb) were used in a 69-d growth assay with 7 pigs per pen and 4 pens per treatment. Treatments were a corn-soybean meal-based control and diets having 40% sorghum-based DDGS (U.S. En-ergy Partners, Russell, KS) without and with 5% added tallow or palm oil. Feed and water were consumed on an ad libitum basis until pigs were slaughtered (average BW 283 lb) to allow collection of carcass data and jowl samples. Fatty acid composition of jowl samples was used to calculate iodine value (IV) as an indicator of carcass fat firmness. Overall (d 0 to 69), the corn-soybean control supported greater ADG and ADFI (P<0.001) with no difference in F/G (P>0.9) compared with the DDGS treatments. Adding 5% beef tallow and palm oil to diets with DDGS improved overall F/G (P<0.02). Pigs fed the control diet had greater (P<0.04) HCW and dressing percentage than pigs fed the DDGS treatments. Adding fat to DDGS diets tended to improve dressing percentage (P<0.07), but there were no effects of fat source on carcass measurements (P>0.14). Changes in IV indicated softer fat in pigs fed DDGS (P<0.001) than in pigs fed the control diet even when sources of saturated fatty acids were added to the diets. For Exp. 2, 112 barrows (initially 150 lb) were used in a 67-d growth assay with 7 pigs per pen and 4 pens per treatment. Treatments were the same as in Exp. 1, but fat sources were stearic acid and coconut oil. At slaughter (av-erage BW 270 lb), in addition to collection of carcass data and jowl samples, belly firmness was determined by using a subjective scoring system and by measuring the distance from tip to tip of the belly after it was drooped over a 1-in.2 bar for 5 min. The corn-soybean control tended to support greater overall ADG (P<0.09) with no difference in ADFI and F/G (P>0.14) compared with DDGS treatments. Adding fat sources to diets with DDGS tended to improve (P<0.06) overall F/G, and coconut oil improved F/G compared with stearic acid (P<0.001). Pigs fed the control diet had greater (P<0.05) HCW than pigs fed the DDGS treatments. Pigs fed the control diet had lower IV and greater firmness score than pigs fed diets with added DDGS (P<0.02). Adding fat sources to diets with DDGS improved these estimates of carcass firmness and tip to tip distance for suspended bellies (P<0.001); coconut oil had a much greater effect than stearic acid (P<0.001). In conclusion, adding beef tallow, palm oil, and coconut oil to diets with 40% DDGS improved efficiency of gain in finishing pigs. However, only coconut oil restored carcass firmness to levels at or above a corn-soybean diet without DDGS.; Swine Day, 2008, Kansas State University, Manhattan, KS, 2008
Keywords: Swine day; 2008; Kansas Agricultural Experiment Station contribution; no. 09-074-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1001; Carcass firmness; Coconut oil; Dried distillers grains with solubles; Palm oil